Hepatitis C virus increases the risk of kidney disease among HIV‐positive patients: Systematic review and meta‐analysis. Issue 3 (8th October 2015) - Fabrizi, Fabrizio; Dixit, Vivek; Martin, Paul; Messa, Piergiorgio
Abstract : Kidney disease has become an important co‐morbidity among human immunodeficiency virus‐infected patients as they live longer in the era of highly effective antiretroviral therapy. It remains unclear how co‐infection with hepatitis C virus impacts on the trajectory of kidney disease among HIV‐infected patients. To evaluate the effect of co‐infection with HCV on the risk of kidney disease in HIV‐infected populations. We conducted a systematic review of the published medical literature to determine if hepatitis C co‐infection is associated with increased likelihood of chronic kidney disease in HIV‐positive adults. We used the random effects model of DerSimonian and Laird to generate a summary estimate of the relative risk for chronic kidney disease (defined by reduced glomerular filtration rate and/or detectable proteinuria) with hepatitis C virus across the published studies. Meta‐regression and stratified analysis were also conducted. We identified 19 studies (146, 151 unique patients with HIV) and separate meta‐analyses were performed according to the outcome. Aggregation of longitudinal studies (n = 8, 105, 462 unique patients) showed a relationship between HCV infection and increased risk of reduced glomerular filtration rate among HIV‐infected individuals, the summary estimate for adjusted hazard ratio was 1.64 (95%CI, 1.28; 2.0, P < 0.001) in HIV‐HCV co‐infected individuals compared with those having HIV mono‐infection. No between‐studies heterogeneity was noted ( P ‐value by Q test = 0.08). HCV positive serology was an independent risk factor for proteinuria; adjusted effect estimate, 1.23 (95% confidence interval, 1.18; 1.28, P = 0.001) (n = 6 studies; 26, 835 unique patients). In meta‐regression, we noted the impact of ageing ( P = 0.0001) upon the adjusted hazard ratio of incidence of reduced glomerular filtration rate among HCV‐HIV co‐infected patients; a negative association between frequency of males ( P = 0.001) and the adjusted hazard ratio of prevalence of low glomerular filtration rate was found. Hepatitis C co‐infection is associated with a significant increase in the risk of reduced glomerular filtration rate and/or detectable proteinuria among HIV‐infected individuals. J. Med. Virol. 88:487–497, 2016 . © 2015 Wiley Periodicals, Inc.